Understanding the Interplay between the Digital and the Physical in Shared AR Gaming: Probing through Urban Legends - Xu, Jiangnan; Luna, Sanzida Mojib; Tigwell, Garreth W.; Lalone, Nicolas; Saker, Michael; Laato, Samuli; Dunham, John; Wang, Yihong; Chamberlain, Alan; Papangelis, Konstantinos (Association for Computing Machinery (ACM), 2026)
Shared Augmented Reality (Shared AR) is an emerging technology that enables multiple users to interact synchronously within a collocated AR environment. Yet, there is limited research on the group interactions and dynamics in Shared AR, particularly in the context of gaming. To address this gap, we investigate Shared AR group interactions using a phone-based Shared AR mobile game called Urban Legends. Through in situ observations, focus groups, and one-on-one interviews with 22 participants, we examine how users collaborate and communicate within the game. Our findings reveal that while verbal communication predominates, non-verbal cues are often overlooked by collocated participants, and users initially struggle to recognize the expansive virtual space and the need for physical movement. Over time, users adapt to the hybrid environment, demonstrating increasing spatial awareness and more dynamic collaboration. Based on these insights, we present a suite of design recommendations for enhancing spatial awareness, supporting multi-modal communication, and fostering engaging group dynamics in future Shared AR applications.